Gambaran Pemberian Makanan Enteral pada Pasien Dewasa di RSUP DR. Sarjito Yogyakarta - Purnomo, Roni; Styowati, Sri; Effendy, Christantie (Jurnal Keperawatan Soedirman, 2007)
A high prevalence of malnutrition in hospitals leads to the increasing of more attention paid for nutrition management. Enteral nutrition feeding in a proper way will give advantages such as protecting nutrition status in order not to go worse and preventing or reducing the occurrence of metabolic complication and infection. It requires specific knowledge and expertise in nutrition area, management of enteral nutrition feeding is a part of nurse’s responsibilities. This study was aimed to obtain a description of technical feeding of enteral nutrition to adult patient at DR. Sardjito Hospital Yogyakarta. The type of this study was descriptive explorative by means of quantitative method, data was collected through observation to research subject who are the patients undergoing enteral nutritional therapy with a total number of 21 patients. This study was done within December 19th 2005 – January 9th 2006. The result showed that a high percentage of enteral nutrition feeding done by family was 40 actions (63.49%) while that done by nurses was 23 actions (36.51%). Enteral nutrition feeding that was considered as properly done was only 20 actions (31.75%) while that considered as improperly done was 43 actions (68.25%). The most frequent things that were not done in enteral nutrition feeding were checking the intestinal distortion before and after the nutrition feeding, aspirating residual volume of stomach before nutrition feeding, considering the rate of feeding, and some did not set the position of semifowler (30o – 45o) during enteral nutrition feeding. This study showed that most of enteral feeding had not been done based on theoretical standard.